Incidence of Acute Kidney Injury in Patients with Chronic Renal Insufficiency: Transcatheter versus Surgical Aortic Valve Replacement. (23rd April 2019) - Catalano, Michael; Lin, Dishen; Cassiere, Hugh; Kohn, Nina; Rutkin, Bruce; Maurer, Greg; Berg, Jacinda A.; Jahn, Jaclyn; Esposito, Rick; Hartman, Alan; Yu, Pey-Jen
Abstract : Objectives . The objective of this study is to determine incidence of acute kidney injury (AKI) associated with transcatheter aortic valve replacement (TAVR) versus surgical aortic valve replacement (SAVR) in patients with preexisting chronic kidney disease. Background . The incidence of AKI in patients with preexisting renal insufficiency undergoing TAVR versus SAVR is not well described. Methods . All patients with preexisting chronic kidney disease who underwent SAVR for aortic stenosis with or without concomitant coronary artery bypass grafting or TAVR from 5/2008 to 6/2017. Patients requiring preoperative hemodialysis were excluded. Chronic kidney disease was defined as an estimated glomerular filtrate rate (eGFR) of < 60 mL/min/1.73 m 2 . The incidence of postoperative AKI was compared using the RIFLE classification system for acute kidney injury. Results . A total of 406 SAVR patients and 407 TAVR patients were included in this study. TAVR patients were older and had lower preoperative eGFR as compared to SAVR patients. Covariate adjustment using propensity score between the two groups showed that SAVR patients were more likely to have a more severe degree of postoperative AKI as compared to TAVR patients (OR = 4.75; 95% CI: 3.15, 7.17; p <.001). SAVR patients were more likely to require dialysis postoperatively as compared to TAVR patients (OR = 4.55; 95% CI: 1.29, 15.99; p <.018). Conclusion . In patients with preexisting chronic kidney disease, TAVR was associated with significantly less AKI as compared to SAVR.